(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
The capability of sawdust for removal of Reactive Yellow (RY 1) and Acid Orange (AO2), from aqueous solutions was studied. The effect of various experimental parameters such as different treatments of sawdust, sorbent dose and pH of solution were studied. The saw dust a relatively abundant and inexpensive material was found to be effective absorbent for the removal of reactive and acid dyes from their aqueous solutions. It was found that the sawdust activated with acid have higher adsorption capacity. It has been found that at initial pH of 2 and at higher sorbent dose reactive and acid dyes were removed more effectively. Key words: Sawdust; Adsorption; Dye removal; Sorbent dose. DOI: 10.3329/bjsir.v45i1.5181 Bangladesh J. Sci. Ind. Res. 45(1), 35-38, 2010